Development and evaluation of azithromycin dihydrate in single and binary micellar mediums - M. Sobika; E. Paul Raj; Sivakumar Krishnamoorthy; Sasmita Dash (Chemical Physics Impact, 2023)
Azithromycin (AZI) has poor aqueous solubility and very low bioavailability. In this study, two nonionic polymeric surfactants, namely Pluronic L-35, and Pluronic P-123, and their binary micelle was used for entrapment of drug AZI. The drug-encapsulated micelles were characterized by UV-spectrophotometry, FTIR, Cloud point, Partition coefficient, and antibacterial studies. We observed improved solubilization of the drug AZI in the binary micellar formulation than in their single micellar systems. The FTIR studies inferred that there is a stable, strong bond formation of the drug AZI with the binary micelle. The partition coefficient values too pointed towards higher solubility of drug AZI in mixed micellar systems as compared to single micellar systems. The free energy of micellization ∆Gomic as determined from the partition coefficient displayed negative values for all three systems indicating spontaneous binding between the drug AZI with the polymeric micellar systems. The highest negative value (-3192.6 kJ/mol) for AZI in the binary system compared to AZI-L-35 (-1620.3 kJ/mol) and AZI-P-123 (-2752.8 kJ/mol) concludes that the drug AZI is better partitioned in the binary micellar system than in the two single micellar solutions. This study can be considered as a potential solubilizing medium for the drug AZI. This is probably the first report of AZI in binary micellar solution.